Scleral buckling with adjuvant pneumatic retinopexy versus scleral buckling alone for rhegmatogenous retinal detachment - Young Hoon Jung; Kyu Hyung Park; Se Joon Woo; Kwangsic Joo; Min Seok Kim (Scientific Reports, 2024)
Abstract To compare the efficacy of scleral buckling with adjuvant pneumatic retinopexy (SB with PR) and scleral buckling (SB) alone for primary rhegmatogenous retinal detachment (RRD). This retrospective and comparative study included patients who underwent SB with PR (n = 88) or SB alone (n = 161) for primary RRD. The primary anatomical success rate for SB with PR was 81.8%, whereas that for SB alone was 80.7% (P = 0.836). Among patients who achieved primary anatomical success, those in the SB with PR group showed postoperative epiretinal membrane (ERM) formation more frequently than those in the SB alone group (11 of 72 [15.3%] vs. 6 of 130 [4.6%]) (P = 0.009). The mean time to subretinal fluid absorption was not significantly different between the SB with PR and SB alone groups (11.2 ± 6.2 vs. 11.4 ± 5.8 months, P = 0.881). In the SB with PR group, retinal detachment involving ≥ three quadrants was a significant risk factor for surgical failure (hazard ratio, 3.04; P = 0.041). Adjuvant pneumatic retinopexy does not provide additional benefit in improving the surgical outcomes of SB for primary RRD repair.